Development of Digital Storytelling Based on Local Wisdom for Strengthening the Pancasila Student Profile in High Schools throughout Kediri Regency - Ganes Tegar Derana; Angellia Ratna Putri Yurita (Adjektiva: Educational Languages and Literature Studies, 2026)
This research is motivated by the urgency of moral value degradation among Generation Z amidst the massive wave of digitalization, as well as the need for learning media innovations that are aligned to strengthen the achievement of the Pancasila Student Profile (P5) in Senior High Schools (SMA). This study aims to develop, test the feasibility, and evaluate the effectiveness of Digital Storytelling (DST) media based on local wisdom, specifically the Panji Kediri Story Cycle. The approach used is Research and Development (R&D) with the ADDIE model framework (Analysis, Design, Development, Implementation, Evaluation). Data collection was conducted comprehensively through expert validation sheets, practicality response questionnaires, as well as observation and self-assessment rubrics to measure the dimensions of Critical Thinking and Global Diversity. The validation results showed a feasibility level predicated as "Very Valid" from content experts (89%) and media experts (92%), accompanied by the practicality level from users as much as 91%. Field effectiveness tests confirmed a significant shift in the achievement of affective character; the percentage of students in the categories 'Developing as Expected' and 'Highly Developed' sharply increased from 35% to 82% post-intervention. This study concludes that integrating local wisdom into Digital Storytelling media successfully deconstructed dogmatic moral learning into reflective visual experiences. This innovation has been proven effective as a pedagogical instrument that bridges the noble values of the nation with the psychological characteristics of students in the digital era.